2006
DOI: 10.1042/bc20050032
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of specific inositol 1,4,5‐trisphosphate receptor isoforms on cellular Ca2+ signals

Abstract: Background information. Oscillations of cytosolic Ca2+ are well-known to rely on the regulatory properties of the InsP 3 R (inositol 1,4,5-trisphosphate receptor). imply different dynamical behaviours when these receptors are present in a cellular environment. We therefore describe by a specific phenomenological model the three main types of curves that have been reported: (i) the classical bell-shaped curve, (ii) the bell-shaped curve that is shifted towards higher Ca 2+ concentrations when InsP 3 is increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In our study, we never observed InsP 3 production oscillations, and these results are in good agreement with studies in airway smooth muscle, where muscarinic receptor-induced calcium oscillations of similar frequencies do not rely on InsP 3 oscillations [18]. The described intrinsic properties of the InsP 3 R subtypes can be helpful to explain Ca 2+ oscillations activated by ACh, especially their bell-shaped regulation by Ca 2+ [4,19,24,25]. We have previously shown that in vascular myocytes expressing InsP 3 R1 and InsP 3 R2, Ca 2+ oscillations are activated by ACh challenges [5].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we never observed InsP 3 production oscillations, and these results are in good agreement with studies in airway smooth muscle, where muscarinic receptor-induced calcium oscillations of similar frequencies do not rely on InsP 3 oscillations [18]. The described intrinsic properties of the InsP 3 R subtypes can be helpful to explain Ca 2+ oscillations activated by ACh, especially their bell-shaped regulation by Ca 2+ [4,19,24,25]. We have previously shown that in vascular myocytes expressing InsP 3 R1 and InsP 3 R2, Ca 2+ oscillations are activated by ACh challenges [5].…”
Section: Discussionsupporting
confidence: 93%
“…Based on experimental data, mathematical models have been generated [17,18], and three models of Ca 2+ oscillations induced by agonist stimulation of the InsP 3 pathway are generally proposed: (1) Ca 2+ oscillations are due to the regulation of InsP 3 R by Ca 2+ itself [19]. (2) Ca 2+ oscillations are activated by InsP 3 oscillations.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the observed steady-state open probabilities, modeling has allowed to link the changes in the overall Ca 2+ dynamics observed after modification of the levels of expression of the various subtypes to their different regulations by InsP 3 and Ca 2+ (Dupont and Combettes, 2006). Thus, type 2 receptor, which shows the sharpest dependence on cytosolic Ca 2+ and has the highest affinity for InsP 3 is the main oscillatory unit, as shown in DT40 cells (Miyakawa et al, 1999) and myocytes (Morel et al, 2003).…”
Section: Oscillationsmentioning
confidence: 99%
“…In a cell type where the total receptor density ͑InsP 3 R1 + InsP 3 R2 + InsP 3 R3͒ is low (Fig. 2, right panels), the constant Ca 2+ flux provided by type 3 receptors could activate types 1 and 2 and thereby favor Ca 2+ oscillations (Dupont and Combettes, 2006). This prediction might be related to the observation performed in pancreatic acinar cells that the addition of both InsP 3 R2 and InsP 3 R3 support Ach and CCK-induced Ca 2+ oscillations (Futatsugi et al, 2005).…”
Section: Oscillationsmentioning
confidence: 99%
“…However, such models did not include the interaction of the dimerized receptors with G proteins or the subsequent complex intracellular signaling systems but they mainly focused on the kinetics of receptor binding and dimerization. With increasing understandings of the signaling systems between GnRH binding and LH release [7,15] . perfusion systems development and optical methods to study the changes in cytosolic Ca 2+ content of individual gonadotropes has allowed much new data to be obtained on the changes in cytosolic Ca 2+ concentration (CAC) and the rates of release of LH in response to short pulses of GnRH.…”
Section: +mentioning
confidence: 99%